Women and Ritual Purity in Islam - Stella Eme Osim; Nzeyo Gabriel Eteng (Indonesian Journal of Social and Educational Studies, 2021)
Purity is a beautiful word that is pleasing to the eye, and a quality that everyone wishes to maintain. From an Islamic perspective, purity has a general meaning. Thus it may mean, on one hand, physical cleanliness which is the purity (of the body) from perceptible filth or ritual purification. On the other hand, it may mean spiritual purity which is the purity of the self from vices, sins and abandoning disobedience, and getting used to good deeds and words. Purity (Arabic: طهارة‎, ṭahāra is an essential aspect of Islam. It is the opposite of najāsa, the state of being ritually impure. It is achieved by first removing physical impurities (for example, urine) from the body, and then removing ritual impurity by means of wudu (usually) or ghusl. Rules which regulate the cleanliness rituals are placed both by Quranic requirements, and the rituals to acquire a new level of social status in everyday Muslim life. Physically, spiritually, ethically, and psychologically every Muslim must value cleanliness and purity. In this work, I investigate the concept of “purity” from the Islamic perspective. I argue that cleanliness and purity form an essential ideal in Muslim piety and consciousness. The Qur'an frequently refers to it.